(598) Monograph on the Theory of Storage دراسة عن نظرية التخزين - Anis, Abd El-Azim (INP, 2024)
The theory of storage, associated with dams built to store water, has evolved into two related branches over the past fifteen years. Some of the earliest problems were raised by H.E. Hurst and later developed and solved by Lloyd, Anis, and Solari. A summary of these results will be provided later in the monograph. However, the stochastic theory of dams was initiated by Moran and his school. Since then, the literature on storage has expanded significantly. Moran succeeded in constructing a model, with the involved assumptions, that can be regarded as a first approximation to the real situation faced in civil engineering. In this model, it is assumed that we have a reservoir with a finite capacity k, and the inflow of water (X) at time t is a random variable with a specified distribution function.